2015
DOI: 10.1242/jeb.120576
|View full text |Cite
|
Sign up to set email alerts
|

Body mass affects seasonal variation in sickness intensity in a seasonally-breeding rodent

Abstract: Species that display seasonal variation in sickness intensity show the most intense response in the season during which they have the highest body mass, suggesting that sickness intensity may be limited by an animal's energy stores. Siberian hamsters (Phodopus sungorus) display lower body masses and less intense sickness when housed in short, winter-like days as opposed to long, summer-like days. To determine whether reduced sickness intensity displayed by short-day hamsters is a product of seasonal changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…In house sparrows ( Passer domesticus ), glucocorticoid treatment suppresses cell-mediated immunity in birds inhabiting temperate, but not tropical, regions (Martin et al, 2005). In a reciprocal NEI interaction, plasma glucocorticoid level following bacterial lipopolysaccharide challenge is higher in Siberian hamsters ( Phodopus sungorus ) adapted to short day lengths (winter-like conditions) versus long day lengths, suggesting a photoperiodic effect (Carlton and Demas, 2015a). In tree lizards, corticosterone suppresses wound healing only during periods of energy limitation, implying a reorganization of the NEI circuit when resources are abundant (French et al, 2007).…”
Section: Nei Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…In house sparrows ( Passer domesticus ), glucocorticoid treatment suppresses cell-mediated immunity in birds inhabiting temperate, but not tropical, regions (Martin et al, 2005). In a reciprocal NEI interaction, plasma glucocorticoid level following bacterial lipopolysaccharide challenge is higher in Siberian hamsters ( Phodopus sungorus ) adapted to short day lengths (winter-like conditions) versus long day lengths, suggesting a photoperiodic effect (Carlton and Demas, 2015a). In tree lizards, corticosterone suppresses wound healing only during periods of energy limitation, implying a reorganization of the NEI circuit when resources are abundant (French et al, 2007).…”
Section: Nei Phenotypesmentioning
confidence: 99%
“…The status of energy stores becomes more important as immune activation progresses and is conveyed through metabolic hormones, such as leptin and ghrelin (Carlton et al, 2012). Lower energy stores can lead to the termination of sickness behavior; otherwise, survival is drastically reduced once body mass (and energy stores) decreases below a minimum threshold (Ashley and Wingfield, 2012; Carlton and Demas, 2015a). …”
Section: Acute Phase Response and Sickness Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that food restriction results in suppression of sickness symptoms (Bilbo and Nelson, 2002; MacDonald et al, 2014; MacDonald et al, 2011). Additionally, the intensity of the energetically costly symptoms of sickness are correlated with body mass in several species, such that animals with higher body masses show more intense sickness responses (Carlton and Demas, 2015; Owen-Ashley et al, 2008; Owen-Ashley et al, 2006; Pohl et al, 2014). Siberian hamsters ( Phodopus sungorus ) are a species that shows variation in sickness intensity that correlates with energetic state.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hamsters show seasonal variation in both body mass and sickness intensity and exhibit the most intense sickness responses in the season in which they have the greatest body mass (Bilbo et al, 2002). We have previously manipulated body mass and an endocrine signal of fat stores (i.e., leptin) to determine their effects on sickness intensity variation in this species (Carlton and Demas, 2014; Carlton and Demas, 2015). These studies showed that hamsters modulate sickness symptoms in response to decreases in energy stores (i.e., attenuation of sickness-induced anorexia and body mass loss in hamsters that were food restricted to lose body mass; Carlton and Demas, 2015) and increases in circulating leptin levels (i.e., attenuation of sickness-induced hypothermia in hamsters provided exogenous leptin to simulate increased fat stores; Carlton and Demas, 2014).…”
Section: Introductionmentioning
confidence: 99%